IDNLearn.com: Your trusted source for finding accurate answers. Discover detailed answers to your questions with our extensive database of expert knowledge.

Solve the equation:

[tex]\[ y + 6 = -3y + 26 \][/tex]

A. [tex]\( y = -8 \)[/tex]

B. [tex]\( y = -5 \)[/tex]

C. [tex]\( y = 5 \)[/tex]

D. [tex]\( y = 8 \)[/tex]


Sagot :

Sure, let’s solve the equation step-by-step.

We start with the given equation:
[tex]\[ y + 6 = -3y + 26 \][/tex]

1. Combine like terms on one side:
First, we want to get all terms involving [tex]\( y \)[/tex] on one side of the equation and constant terms on the other side. To do this, add [tex]\( 3y \)[/tex] to both sides of the equation:
[tex]\[ y + 6 + 3y = -3y + 3y + 26 \][/tex]
[tex]\[ 4y + 6 = 26 \][/tex]

2. Isolate the term with [tex]\( y \)[/tex]:
To solve for [tex]\( y \)[/tex], we need to isolate the variable term. Subtract 6 from both sides of the equation:
[tex]\[ 4y + 6 - 6 = 26 - 6 \][/tex]
[tex]\[ 4y = 20 \][/tex]

3. Solve for [tex]\( y \)[/tex]:
Divide both sides of the equation by 4 to solve for [tex]\( y \)[/tex]:
[tex]\[ \frac{4y}{4} = \frac{20}{4} \][/tex]
[tex]\[ y = 5 \][/tex]

So the solution to the equation [tex]\( y + 6 = -3y + 26 \)[/tex] is:
[tex]\[ y = 5 \][/tex]

Hence, the correct answer is:
[tex]\[ y = 5 \][/tex]
We appreciate your contributions to this forum. Don't forget to check back for the latest answers. Keep asking, answering, and sharing useful information. IDNLearn.com is committed to your satisfaction. Thank you for visiting, and see you next time for more helpful answers.